Fluid biopsy versus conventional biopsy – a revolutionary approach in oral cancer diagnosis: a systematic review and meta-analysis - Hazarika, Silviya; Mahesh, Shakila (Journal of Stomatology, 2026)
Early detection of oral cancer is critical for improving treatment outcomes and reducing the risk of malignant transformation. Liquid biopsy (LB), a minimally invasive diagnostic tool, offers significant promise for early diagnosis and disease monitoring. However, a lack of comprehensive synthesis comparing the diagnostic performance of various LB biomarkers in oral cancer as well as the absence of standardized sampling techniques, creates variability in clinical application. This systematic review and meta-analysis critically evaluated the diagnostic performance and clinical utility of LB biomarkers, including circulating tumor cells, cell-free DNA, microRNAs, messenger RNA, and salivary exosomes. Studies assessing sensitivity, specificity, diagnostic accuracy, and reproducibility were included, along with evaluations of methodological inconsistencies, operational challenges, and infrastructure requirements. The findings revealed that while LB demonstrates substantial potential for early detection and monitoring, the variability in sensitivity, specificity, and reproducibility remain a significant barrier. The lack of standardized pre-analytical and analytical protocols further undermines diagnostic reliability. Implementation challenges also stem from infrastructural demands and the need for specialized training. In conclusion, LB could revolutionize oral cancer diagnosis and management. However, standardized protocols, large-scale validation studies, and infrastructural investments are urgently needed to enhance diagnostic accuracy, facilitate early intervention, and ultimately improve patient outcomes.